Growth Hormone Treatment: First Results of the Partnership Program for the Establishment of a Growth Center at the University Clinic of Pediatrics –Pleven - Irina Halvadzhiyan (Journal of Biomedical & Clinical Research, 2021)
In March 2018, in the Clinic of Pediatrics of the University Hospital “G. Stranski ”- Pleven, we have created a Center for diagnosing and treating children with growth disorders, in active collaboration with an established expert center. During the study, 53 children with height 0.05), living mainly in cities. For 18 months, we treated a total of 11 children (54.5% male) with an average age at the start of GH therapy of 8.1 ± 4.4 years and an average growth velocity of 10.3 ± 7.7 cm/year. Treatment with GH was introduced in Pleven after successfully establishing the Growth Center in the Clinic of Pediatrics. The first results showed a significant increase in the number of diagnosed and treated children whose follow-up we found an acceleration in growth and bone maturation, positive body composition changes, and lack of side effects from the treatment.